Takhrij Hadith Study: Partial and Simultaneous Analysis of the Sujud Hadith narrated by Abu Hurairah in Sunan Abu Dawud - Abdulloh Safiq; Abdul Khamid; M. Miftakhul Huda (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
The background of this study relates to the analysis of the quality of a hadith regarding the movement of sujud, specifically concerning the precedence of placing the hands before the knees, which is an important topic in the fiqh of prayer. This study aims to conduct both partial and simultaneous analyses of the hadith narrated by Abu Hurairah and authenticated by Imam Abu Dawud. The research method employed is documentation to collect data related to the hadith and the reliability of its narrators, along with content analysis to examine the data. The findings indicate that, in the partial analysis, this hadith is classified as sahih lidzatih, as all narrators are trustworthy (tsiqa), the chain of narration (sanad) is continuous (muttasil), and the text (matan) does not contain any irregularities (syaz) or defects ('illat). The simultaneous analysis reveals three supporting narrations (tabi'), yet the quality of the hadith remains sahih despite these supporting narrations not having an impact. The study also identifies two corroborating hadiths narrated by Ibn Umar and Barra’, further strengthening the authenticity of the hadith. The contribution of this research lies in providing empirical evidence regarding the quality and validity of the hadith related to the sujud movement in prayer.